Sorption and Desorption of the Model Aromatic Hydrocarbons Naphthalene and Benzene: Effects of Temperature and Soil Composition - Shi, Bingjie; Ngueleu, Stephane K.; Rezanezhad, Fereidoun; Slowinski, Stephanie; Pronk, Geertje Johanna; Smeaton, Christina M.; Stevenson, Krista; Al-Raoush, Riyadh I.; Van Cappellen, Philippe (Frontiers in Environmental Chemistry, 2020)
Petroleum hydrocarbon (PHC) contamination is a global environmental issue. Understanding the key factors and mechanisms controlling the fate and mobility of PHCs in soils and aquifers is critical for environmental risk assessment, the development of remediation strategies, and policy decisions. This study focuses on the effects of soil composition and temperature on the sorption and desorption of two representative aromatic PHC compounds: benzene and naphthalene. The experiments were carried out using artificial sandy loam soil mixtures with temperatures ranging from 3 to 25℃. As expected, the sorption capacities of the soils were primarily controlled by the organic carbon (OC) content, while barely affected by the clay content. The sorption data for benzene and naphthalene followed linear to near-linear isotherms. Naphthalene sorption further increased with decreasing temperature, whereas temperature had little effect on benzene sorption. The latter was consistent with the very small magnitude of the sorption enthalpy of benzene. Under imposed dynamic temperature fluctuations, naphthalene sorption and desorption were shown to be reversible: model simulations demonstrated minimal kinetic limitation of the temperature-dependent soil-water partitioning. Our results imply that even in simple artificial soil systems, temperature variations can have complex, but predictable, effects on the soil-pore water partitioning of PHCs and, hence, on their mobility and bioavailability. Understanding the role of temperature is thus a prerequisite to unraveling the coupled abiotic and biotic processes that modulate the fate of PHCs in real-world soils.